Thoracic trauma: analysis of 100 consecutive cases - Scapolan,Maíra Benito (2010)
ABSTRACT Objective: To analyze thoracic trauma assisted by the Emergency Service of Hospital da Irmandade da Santa Casa de Misericórdia de São Paulo. Methods: One hundred patients with thoracic trauma were assisted throughout six months in 2006. Data from their records were collected and a protocol of thoracic trauma was fulfilled. The Revised Trauma Score was used to evaluate gravity of injury and to calculate the survival index. Results: Prevalence of trauma injury in male from 20 to 29 years old was observed. Out of all patients, 44 had blunt trauma and 56 penetrating trauma (78.6% presented stab wounds and 21.4% gun shots). Up to the settings of injuries, 23% were in the thoracoabdominal transition, 7% in the precordium and 70% in the remainder thoracic area. In those with the thoracoabdominal transition injury, 22.7% were hemodynamically unstable and 77.3% stable. Thoracoabdominal injury patients presented 40.9% of diaphragm wound and all were stable. Of those with precordium wound, 37.5% presented cardiac injury. In cardiac onset, 66.7% presented stable and 33.3% unstable. Thoracic drainage was the most accomplished surgical procedure (71%). Conclusions: The thoracic trauma patient is most prevalently young male with stab wound penetrating injury, without associated injuries, hemodynamically stable, presenting hemothorax, with high probability of survival.